Advances in the roles of glycyrrhizic acid in cancer therapy - Zhang, Yuqian; Sheng, Zixuan; Xiao, Jing; Li, Yang; Huang, Jie; Jia, Jinjing; Zeng, Xiansi; Li, Li (Frontiers in Pharmacology, 2023)
Since the first 70 years of reporting cancer chemotherapy, malignant tumors have been the second most common cause of death in children and adults. Currently, the commonly used anti-cancer methods include surgery, chemotherapy, radiotherapy, and immunotherapy. Although these treatment methods could alleviate cancer, they lead to different forms of side effects and have no particularly significant effect on prolonging the patients' life span. Glycyrrhizic acid (GL), a native Chinese herbal extract, has a wide range of pharmacological effects, such as anti-cancer, anti-inflammatory, antioxidant, and immune regulation. In this review, the anti-cancer effects and mechanisms of GL are summarized in various cancers. The inhibition of GL on chemotherapy-induced side effects, including hepatotoxicity, nephrotoxicity, genotoxicity, neurotoxicity and pulmonary toxicity, is highlighted. Therefore, GL may be a promising and ideal drug for cancer therapy.